2006
DOI: 10.1177/0748730406294418
|View full text |Cite
|
Sign up to set email alerts
|

No Promoter Left Behind: Global Circadian Gene Expression in Cyanobacteria

Abstract: Prokaryotic cyanobacteria express robust circadian (daily) rhythms under the control of a clock system that appears to be similar to those of eukaryotes in many ways. On the other hand, the KaiABC-based core cyanobacterial clockwork is clearly different from the transcriptiontranslation feedback loop model of eukaryotic clocks in that the cyanobacterial clock system regulates gene expression patterns globally, and specific clock gene promoters are not essential in mediating the circadian feedback loop. A novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 64 publications
1
49
0
Order By: Relevance
“…Therefore, the plasmid topology rhythm is conditionally coupled to the core KaiABC circadian oscillator in a light-dependent manner (12). In DD, the core oscillator can continue to ''tick'' but is uncoupled from its ability to modulate changes in plasmid topology and other clock outputs as well, most significantly, the global rhythm of gene expression (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the plasmid topology rhythm is conditionally coupled to the core KaiABC circadian oscillator in a light-dependent manner (12). In DD, the core oscillator can continue to ''tick'' but is uncoupled from its ability to modulate changes in plasmid topology and other clock outputs as well, most significantly, the global rhythm of gene expression (24).…”
Section: Discussionmentioning
confidence: 99%
“…Although microarrays are informative, this technique is not sensitive to small changes in mRNA abundance and is not a quantitative measure of rhythmic transcriptional activity for mRNAs that are either very unstable or very stable. Because of these limitations of microarrays, the degree to which circadian clocks control promoter activity is likely to have been underestimated in eukaryotes (12,13). Because the promoter trap technique measures promoter activity, its application in S. elongatus may explain why pervasive clock control over gene expression has been found in cyanobacteria, but not in eukaryotic circadian systems.…”
mentioning
confidence: 99%
“…The lowamplitude and bright (LabA) protein is proposed to act in a repression pathway to feed temporal information Output. The cyanobacterial circadian clock regulates global gene expression, such that every promoter tested drives expression of luciferase reporter genes in a 24-hour rhythm (for review, see Johnson 2004;Woelfle and Johnson 2006). This global control is likely the result of the Kai-dependent circadian rhythm in chromosome compaction that alters the availability of promoter regions to transcriptional machinery (Fig.…”
Section: Inputmentioning
confidence: 99%
“…During the past 15 years, numerous studies have shown that cyanobacteria, photosynthetic microbes, are the only prokaryotes known to have a circadian clock (6,7). Although components of the circadian clock have been identified and analyzed in detail in cyanobacteria (8)(9)(10), the interactions between the clock and cellular physiology and metabolism have not been well elucidated.…”
mentioning
confidence: 99%